Dramatic monologue - Byron, Glennis, 1955- (New critical idiom., 2003)
The dramatic monologue is traditionally associated with Victorian poets such as Robert Browning and Alfred Tennyson, and is generally considered to have disappeared with the onset of modernism in the twentieth century. Glennis Byron unravels its history and argues that, contrary to belief, the monologue remains popular to this day. This far-reaching and neatly structured volume:* explores the origins of the monologue and presents a history of definitions of the term* considers the monologue as a form of social critique* explores issues at play in our understanding of the genr.